2000
DOI: 10.1099/00221287-146-1-233
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two formaldehyde oxidation pathways in Methylobacillus flagellatus KT, a ribulose monophosphate cycle methylotroph The GenBank accession numbers for the sequences of 2502 nt containing gndA and part of zwf, and of 2685 nt containing mch, are AF167580 and AF139592, respectively.

Abstract: The roles of cyclic formaldehyde oxidation via 6-phosphogluconate dehydrogenase and linear oxidation via the tetrahydromethanopterin (H 4 MPT)-linked pathway were assessed in an obligate methylotroph, Methylobacillus flagellatus KT, by cloning, sequencing and mutating two chromosomal regions containing genes encoding enzymes specifically involved in these pathways : 6-phosphogluconate dehydrogenase, glucose-6-phosphate dehydrogenase and methenyl H 4 MPT cyclohydrolase (gndA, zwf and mch). No null mutants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…However, the finding of an alternative system involving N-methylglutamate as an intermediate specifically expressed during growth on methylamine raised a question of whether this additional system contributed to growth on methylamine. The role of the linear pathway for oxidizing formaldehyde has been approached experimentally before (7,18). However, while high activities for the enzymes of the H 4 MPT pathway have been measured, mutants in these enzymes revealed only very subtle phenotypes, suggesting a minor role in formaldehyde oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the finding of an alternative system involving N-methylglutamate as an intermediate specifically expressed during growth on methylamine raised a question of whether this additional system contributed to growth on methylamine. The role of the linear pathway for oxidizing formaldehyde has been approached experimentally before (7,18). However, while high activities for the enzymes of the H 4 MPT pathway have been measured, mutants in these enzymes revealed only very subtle phenotypes, suggesting a minor role in formaldehyde oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics revealed the presence of both GndA (Mfla_0918/Mfla_1062) and GndB (Mfla_2599), the latter seeming to be upregulated in the methylamine-grown cells. We have previously failed to obtain GndA mutants (7). However, in light of the presence of GndB, along with the enzymes for the linear pathway, it appeared necessary to retest the relative contributions of these enzymes to formaldehyde oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In B. methanolicus strain C1, it has been shown that the specific glucose phosphate dehydrogenase activity of the cyclic dissimilatory pathway is three-to fourfold higher in cells growing on methanol than in cells growing on glucose (3). At least four different pathways for bacterial formaldehyde detoxification, including oxidation and fixation, have been described (9,19,20), and it has been shown that some bacteria possess several of these pathways. Interestingly, B. subtilis mutants with yckG or yckF (encoding HPS and PHI activities, respectively) disrupted display only a minor decrease in formaldehyde tolerance, suggesting that the bacterium has alternative biochemical routes for detoxification of formaldehyde (28).…”
Section: Discussionmentioning
confidence: 99%
“…16) There have been only a few reports on the cloning of the genes encoding NAD W NADP dual specic 6PGDH. 7) It seemed that the 6PGDH in this study had higher activity with NAD than that with NADP (Table 1). Adachi et al reported that 6PGDH from Gluconobacter suboxydans IFO 12528 accepted NAD and NADP at almost the same rate.…”
mentioning
confidence: 99%